Exploring environmental factors affecting assistive technology strategies in mathematics learning for students with physical disabilities. - Esquivel, Paola; McGarvey, Lynn; Phelan, Shanon; Adams, Kim (Disability & Rehabilitation: Assistive Technology, 2024)
To explore the environmental facilitators and barriers affecting K-12 students with physical disabilities when using two assistive technology (AT) strategies, LEGO Mindstorms robots and a computer, in mathematics lessons. A qualitative multiple case study with three students with physical disabilities was conducted. The participants did five lessons in concepts they were studying in school with each AT strategy in a controlled environment. Observations of the lessons, and parent and teacher interviews after the last session were collected. The AT strategies acted as facilitators because they were easy to use, participants could participate actively, and parents and school staff wanted to implement them. However, the strategies presented some barriers since the students required more time to complete the lessons with the robot, and some computer programs were not compatible with the students' skills. Also, barriers such as lack of technical knowledge on the part of parents and teachers, distractions in the environment, and funding issues were reported. This study may be useful for rehabilitation staff and teachers who are considering implementing AT to support the participation of students with disabilities. Personnel needs to be trained to use the AT strategies, and several modifications may be necessary for the satisfactory use of the devices. Hands-on manipulation promotes the active learning of early mathematical concepts. Students with disabilities may have the opportunity to participate in active learning through assistive technology (AT). Knowledge about environmental factors that may facilitate or limit the use of AT in the classroom will help teaching staff make decisions when implementing these strategies with students with disabilities. The use of an AT strategy may depend on the objectives the rehabilitation staff and teachers want to achieve during a task. For instance, the robot could be used for tailoring a task according to the student's needs and abilities. On the other hand, computer programs could be considered if time and ease of use are important factors.